(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Linguoculturology is a branch of linguistics that studies the relationship between language and cultural concepts. Cultural linguistics accelerates the theoretical and analytical progress of both cognitive science (including the study of complex systems and processes of cognitive ability distribution) and anthropology. Cultural linguistics explores how different languages use their features to reflect cultural concepts, including cultural models, cultural categories and cultural metaphors. Within the framework of cultural linguistics, language is considered as something rooted in the group, cultural level of cognition.